Risk factors for mortality in blunt abdominal trauma with surgical approach - SILVANIA KLUG PIMENTEL; GUILHERME VINICIUS SAWCZYN; MELISSA MELLO MAZEPA; FELIPE GUILHERME GONÇALVES DA ROSA; ADONIS NARS; IWAN AUGUSTO COLLAÇO (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACTObjective:identify risk factors for mortality in patients who underwent laparotomy after blunt abdominal trauma.Methods:retrospective study, case-control, which were reviewed medical records of blunt trauma victims patients undergoing laparotomy, from March 2013 to January 2015, and compared the result of the deaths group with the group healed.Results:of 86 patients, 63% were healed, 36% died, and one patient was excluded from the study. Both groups had similar epidemiology and trauma mechanism, predominantly young adults males, automobilistic accident. Most cases that evolved to death had hemodynamic instability as laparotomy indication - 61% against 38% in the other group (p=0.02). The presence of solid organ injury was larger in the group of deaths - 80% versus 48% (p=0.001) and 61% of them had other associated abdominal injury compared to 25% in the other group (p=0.01). Of the patients who died 96% had other serious injuries associated (p=0.0003). Patients requiring damage control surgery had a higher mortality rate (p=0.0099). Only one of 18 patients with isolated hollow organ lesion evolved to death (p=0.0001). The mean injury score of TRISS of cured (91.70%) was significantly higher than that of deaths (46.3%) (p=0.002).Conclusion:the risk factors for mortality were hemodynamic instability as an indication for laparotomy, presence of solid organ injury, multiple intra-abdominal injuries, need for damage control surgery, serious injury association and low index of trauma score.